2018
DOI: 10.30560/jems.v1n1p114
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between FDI, Poverty Reduction and Environmental Sustainability in Tunisia

Abstract: Our goal in this paper is the study of the impact of FDI on poverty and sustainable development in the case of Tunisia and during the study period from 1985 to 2015. In addition, we use the test unit root of cointegration test, the model error correction of FMOLS and Granger causality. In the case of Tunisia, we find that all variables are integrated of order 1. Thus, we can use the cointegration test. Indeed, the result of the null hypothesis test of no cointegration was rejected at the 5% threshold, which ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…On the contrary, FDI inflow helped in poverty reduction in Nepal and Sri Lanka while increasing poverty in Pakistan and Bangladesh (Chindengwike, 2022a;Mahmood & Chaudhary, 2012). Lazreg and Zouari (2018) have also proved through unit root test of co-integration, the model error correction of FMOLS and Granger causality that FDI and poverty have negative correlation to each other in Pakistan. (Chindengwike, 2022a) disclosed that FDI was in a positive relation to the poverty alleviation among the developing and underdeveloped countries using time series data analysis from 1987-2017 for Tanzania.…”
Section: Literature Reviewmentioning
confidence: 89%
“…On the contrary, FDI inflow helped in poverty reduction in Nepal and Sri Lanka while increasing poverty in Pakistan and Bangladesh (Chindengwike, 2022a;Mahmood & Chaudhary, 2012). Lazreg and Zouari (2018) have also proved through unit root test of co-integration, the model error correction of FMOLS and Granger causality that FDI and poverty have negative correlation to each other in Pakistan. (Chindengwike, 2022a) disclosed that FDI was in a positive relation to the poverty alleviation among the developing and underdeveloped countries using time series data analysis from 1987-2017 for Tanzania.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Cordier et al (2021) use the adult literacy rate to examine the environmental EKC hypothesis. Lazreg and Zouari (2018) employ the youth literacy rate as a variable of youth power to explore the nexus between FDI and environmental sustainability. Following Wang and Shao (2019), we allow for the constraint of the obtained database and the share of patents in environmental‐related technologies (OECD, 2021).…”
Section: Methodology and Modelmentioning
confidence: 99%
“…[17] states that "FDI has been considered as a powerful engine and a significant catalyst for attaining development, poverty reduction and global integration process. Similarly, [18] assert that FDI in social services such as water and energy is the most credible strategy to fight against poverty in developing nations. [19] assessed what impacts foreign capital may have on income inequality in 54 countries over the period 1980-2005 and found that FDI negatively affects the income of nations with limited absorptive capacity rather than those with strong absorptive capacity.…”
Section: Empirical Review On Fdi and Poverty Nexusmentioning
confidence: 99%